The Quality of English Test Items for Senior High School Students: Validity, Cognitive Level, and Language Skills Analysis - Hevriani Sevrika; Yenni Rozimela; Syahrul R (Darul Yasin Al Sys, 2026)
Although educational assessment has received considerable scholarly attention, comprehensive evaluations of teacher-made English examinations integrating validity, cognitive demand, and language-skill representation remain limited. This study evaluated the quality of a senior high school English summative examination by examining these three dimensions simultaneously. A quantitative descriptive design was employed to analyze all 50 multiple-choice and essay items included in the examination through total sampling. Data were obtained through documentation. Content validity was assessed based on curriculum alignment, empirical validity was examined using Pearson product–moment correlation, cognitive levels were classified according to Bloom’s Revised Taxonomy (C1–C6), and language-skill representation was analyzed using percentage-based descriptive statistics. The findings showed that 38 items (76%) were valid, whereas 12 items (24%) were invalid because of ambiguous wording, poorly constructed distractors, and insufficient alignment with instructional objectives. The cognitive-level distribution was dominated by lower-order thinking skills, particularly understanding (C2; 32%) and remembering (C1; 28%). Higher-order thinking skills were substantially underrepresented, comprising analyzing (C4; 12%), evaluating (C5; 6%), and creating (C6; 2%). The examination also emphasized receptive skills and structural knowledge, with reading comprehension accounting for 48% of the items, followed by grammar (20%) and vocabulary (14%). Productive and communicative skills received considerably less coverage, including writing (10%), listening (6%), and speaking (2%). These findings demonstrate that acceptable item validity alone does not ensure a cognitively balanced and communicatively authentic language assessment. This study contributes to the English language assessment literature by providing a multidimensional evaluation of teacher-made examinations in secondary education. It also highlights the need for teachers, schools, and policymakers to conduct continuous item validation, strengthen assessment literacy, increase higher-order cognitive demands, and achieve a more balanced representation of receptive, productive, and communicative language skills.